A Michael Handelsman: pensador-hacedor-escritor de afán intercultural y decolonial (Tributo) - Walsh McDonald, Catherine Elizabeth (2019)
This letter to Michael Handelsman is an exercise of reflection in which Catherine Walsh writes “co(n)versifying and co-thinking” with said author. The clear purpose is to remember and highlight the literary, intercultural and de-colonial task carried out by Handelsman, with relation to his work as a scholar devoted to Ecuadorian Literature, particularly, Afro-Ecuadorian, without having left aside –despite adopting the aforementioned point of view–, a reading of culture and society as a whole. Walsh’s words arise from a strong critic against literate power and a declared “personal-political-intellectual” empathy with her interlocutor, as privileged places of expression.